Exercise training improves sleep quality: A randomized controlled trial. (12th February 2020) - Jurado‐Fasoli, Lucas; De‐la‐O, Alejandro; Molina‐Hidalgo, Cristina; Migueles, Jairo H.; Castillo, Manuel J.; Amaro‐Gahete, Francisco J.
Abstract: Background: Exercise holds promise as a non‐pharmacological intervention for the improvement of sleep quality. Therefore, this study investigates the effects of different training modalities on sleep quality parameters. Material & methods: A total of 69 (52.7% women) middle‐aged sedentary adults were randomized to (a) control group, (b) physical activity recommendation from the World Health Organization, (c) high‐intensity interval training (HIIT) and (d) high‐intensity interval training group adding whole‐body electromyostimulation training (HIITEMS). Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) scale and accelerometers. Results: All intervention groups showed a lower PSQI global score (all P < .022). HIIT‐EMS group improved all accelerometer parameters, with higher total sleep time and sleep efficiency, and lower wake after sleep onset (all P < .016). No differences were found between groups in any sleep quality parameter. Conclusion: In conclusion, exercise training induced an improvement in subjective sleep quality in sedentary middleaged adults. Moreover, HIIT‐EMS training showed an improvement in objective sleep quality parameters (total sleep time, sleep efficiency and wake after sleep onset) after 12 weeks of exercise intervention. The changes observed in the HIIT‐EMS group were not statistically different to the other exercise modalities.